Identification of resistant donors from South Indian landraces for brown planthopper, Nilaparvata lugens (Stal.), Delphacidae, Hemiptera in rice - Prabu, S; Venugopal, Sheela; Suganthy, M; Suresh, R; Vellaikumar, S; Uma, D; Manonmani, S; Nelson, S Jeyarajan (ORYZA-An International Journal of Rice, 2023)
A total of 126 rice landraces along with resistant (PTB 33) and susceptible (TN 1) check were screened using the protray method. Out of which 13 genotypes having a score of 3.0 - 7.0 were shortlisted and re-evaluated under the modified seed-box screening method. Results of the two experiments showed variation in resistance level with damage score of 3.0 to 9.0. Only one landrace Mysore Malli and PTB 33 were found to be resistant with damage score of 3.0 and four landraces viz., Chetty Samba, Panamara Samba, Vellai Gundu Samba and Vellai Kombi Samba were found to be moderately resistant in both the screening method. In protray screening, 8 landraces were found to be moderately susceptible, 66 landraces were found as susceptible and 48 landraces were highly susceptible. In modified seed-box screening, 5 landraces were found as moderately susceptible, 3 landraces were susceptible and TN 1 in both the methods was found as highly susceptible with a score of 9.0. Cluster analysis performed for 126 landraces based on damage score, nymphal settlement, chlorophyll and Nitrogen content grouped them into six clusters. Among the six clusters, resistant and moderately resistant landraces are grouped in cluster 4 which had low damage score and nymphal settlement and moderate chlorophyll and Nitrogen content.